A hybrid substrate-integrated waveguide and spoof surface plasmon-polariton one-layer dual bandpass filter formed by resonant tunneling effect. (3rd October 2018) - Yang, Zhang-Biao; Guan, Dong-Fang; Zhang, Qingfeng; You, Peng; Hou, Xiao-Xiang; Xu, Shen-Da; Yong, Shao-Wei
Abstract: In this paper, we present a novel dual-bandpass filter based on the substrate-integrated waveguide (SIW) and spoof surface plasmon-polariton (SSPP) hybrid structure. In this design, periodic subwavelength H-shaped units are etched on the top SIW surface to support SSPP mode. The dispersion and transmission characteristics of the proposed SIW–SSPP filter are analyzed. The dual-bandpass feature is observed for resonant tunneling of the H-shaped elements, and the passbands can be controlled easily by adjusting the filter parameters. Simulated and measured results demonstrate excellent transmission performance of the proposed filter.